In vitro evaluation of immunomodulatory activities of goat milk Extracellular Vesicles (mEVs) in a model of gut inflammation. (20th December 2022) - Mecocci, Samanta; De Paolis, Livia; Fruscione, Floriana; Pietrucci, Daniele; De Ciucis, Chiara Grazia; Giudici, Silvia Dei; Franzoni, Giulia; Chillemi, Giovanni; Cappelli, Katia; Razzuoli, Elisabetta
Abstract: Gut represents a major immunological defense barrier with mucosal immune system and intestinal epithelial cells (IECs). In all intestinal diseases, in particular inflammatory bowel disease (IBD), both the absorption and the local immune system are compromised and alternative effective therapies are sought after. Extracellular Vesicles (EVs) have the capability to regulate immune cells within the inflammatory microenvironment, by dampening inflammation and restoring intestinal barrier integrity. Recently, the immune-modulatory role of EVs has also been confirmed for milk EVs (mEVs), notable for their easy production, high sample volumes, cost-effective scalable production and non-toxic and non-immunogenic behavior. In this context, the aim of this study was to evaluate goat mEV anti-inflammatory and immuno-modulating effects on an in vitro model (IPEC-J2) of intestinal inflammation through gene expression evaluation with RT-qPCR and cytokine release dosage with ELISA test. After the establishment of a pro-inflammatory environment due to LPS stimuli, IL6, CXCL8, IL12p35, IL12p40, IFNB, IL18, TLR7 and NOS2 resulted significantly up-regulated in stimulated IPEC-J2 cells compared to those of the basal culture. After 48 h of mEV treatment in inflamed IPEC-J2 a partial restoration of initial conditions was detected, with the IL18 and IL12p40 significant down-regulation, and IL12p35, EBI3, TLR7, BD1 and BD3 up-regulation. IL-18 reduced protein production was also detected in supernatants. Moreover, a decrease of MMP9 and NOS2 together with a strong up-regulation of MUC2 indicated a recovery of cellular homeostasis and, therefore, potential beneficial effects on the intestinal mucosa. Nevertheless, 48 h post-treatment, an increased gene expression and protein release of IL-8 was observed. This paper is one of the firsts to assess the effect of goat mEVs and the first one, in particular, of doing this on an in vitro model of gut inflammation. The obtained results show a potential capability of goat mEVs to modulate inflammation and to play beneficial effects on the intestinal mucosa. Highlights: Goat milk-derived EVs can increase the IPEC-J2 antimicrobial peptides, defensins and toll like receptors Goat milk-derived EVs induce the preferential expression of the anti-inflammatory IL-35 instead of the pro-inflammatory IL-12 Goat milk-derived EVs improve intestinal homeostasis, increasing MUC2 expression and reducing NOS2 and MMP9